2007
DOI: 10.1093/ageing/afm086
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of hospital use: comparison between elderly patients' point of view and a structured questionnaire

Abstract: Appropriateness of hospital use: comparison between elderly patients' point of view and a structured questionnaire SIR-Appropriate use of hospitalisation is a key issue in terms of healthcare resources utilisation and individual needs. Surprisingly, there are only few studies assessing appropriateness of hospital stay in subacute settings. The demographic transition is associated with an increasing number of elderly people with multiple chronic conditions, and a growing need for subacute beds [1, 2]. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The language used -for instance 'bed-blocker' 30 and 'inappropriate admission' 3,4 -and contractual mechanisms designed to incentivize admission avoidance or earlier discharge of older patients from hospital, all reinforce the premise that older people are somehow a 'problem', impairing the functioning of the system by their very presence. 31 Of course, patients of any age should not be in hospital beds unnecessarily.…”
Section: Language and Rhetoricmentioning
confidence: 99%
“…The language used -for instance 'bed-blocker' 30 and 'inappropriate admission' 3,4 -and contractual mechanisms designed to incentivize admission avoidance or earlier discharge of older patients from hospital, all reinforce the premise that older people are somehow a 'problem', impairing the functioning of the system by their very presence. 31 Of course, patients of any age should not be in hospital beds unnecessarily.…”
Section: Language and Rhetoricmentioning
confidence: 99%
“…All participants were told that all data collected would be disposed of securely, and that all personal details would be kept strictly confidential. As a vehicle for questionnaire delivery, the on-line portal consisted of close ended questions to secure a high response rate (Luthy et al, 2007). Structured questionnaires were used in industry and a HEI setting to assess whether participants kept abreast of contemporary fire safety issues.…”
Section: Pilot Studymentioning
confidence: 99%
“…It has been reported that 88% of patients within 48 hours of admission and 85% of patients at 14th day of admission felt that their hospital use was justified, but the appropriateness determined by the appropriateness evaluating protocol was only 37%. 17 Medically inappropriate use of hospital beds can be presented in another form by delaying the discharge instead of increasing admissions. 18 Interestingly, inappropriate medical admission rate was not increased although the acute hospital admission rate was increased, 19 but the medically inappropriate admission was very common among elderly patients with a hospital stay longer than 30 days.…”
mentioning
confidence: 99%